Kondisi fisik dan suasana ruangan di Perpustakaan Fakultas Ekonomika dan Bisnis Universitas Gadjah Mada - Maryatun Maryatun (Jurnal Kajian Informasi dan Perpustakaan, 2018)
The collaborative learning atmosphere in higher education requires adequate facilities such as the availability of comfortable rooms and interior design according to the user needs. The purpose of the study was to discover the user's perceptions of the room’s physical conditions, library facilities and identify spatial requirements, facilities, and the library’s design facilities. This quantitative descriptive study used the purposive sampling technique. The 200 study samples obtained were students of the bachelor, master and doctoral study programs for the class of 2012, 2013, and 2014 who were still active as students. Results showed users' perceptions of the physical condition and atmosphere of the library room agreed on the strategic location, adequate and comfortable lighting system, besides it was beneficial during the study process. Library users required the addition of an independent study room separated from other spaces in the library, availability of electrical plug facility as well as the addition of WiFi. Most of the respondents required a desk in the self-study room, multimedia room, database/internet access room, shared space, support area, and a rectangular student workspace. The study group and discussion rooms required round shaped tables. The furniture’s basic material is wood, and the basic colors are blue, except for the student workspace, which is a combination of brown and white. In conclusion, the users’ perception of the Faculty of Economics and Business Library, Gadjah Mada University is that the location is strategic with adequate lighting. Users need additional self-study rooms and wooden furniture with a blue base color.